The which way tree [large type] - Crook, Elizabeth, 1959- (Wheeler Publishing large print hardcover, 2018)
Early one morning in the remote hill country of Texas, a panther savagely attacks a family of homesteaders, mauling a young girl named Samantha and killing her mother, whose final act is to save her daughter's life. Samantha and her half brother, Benjamin, survive, but she is left traumatized, her face horribly scarred. The Which Way Tree is the story of Samantha's unshakeable resolve to stalk and kill the infamous panther, rumored across the Rio Grande to be a demon, and avenge her mother's death.